DEPENDENCE OF CLICK CHEMISTRY IN THE SYNTHESIS OF BIS-CARBAMATES OF THE MEE SERIES - Eldor Mashaev; Abduhamid Makhsumov; Obidjon Kodirov; Feruz Shapatov (Research Focus International Scientific Journal, 2024)
In this work, the synthesis of bis-carbamates was investigated for the suitability of the mechanism of nucleophilic addition to the requirements of "click chemistry" reactions. As a result, it was concluded that it is expedient to include the synthesis of bis-carbamates that meet all the criteria in "click chemistry" reactions.